Nurses' perception of work with the use of technology in hemodialysis (Research, Society and Development, 2021)
New technologies added to nursing care increase the complexity of the nurse's work while reducing the workload. The aim of this study was to analyze the nurses' perception of working with the use of technology in hemodialysis. The methodology used was a multiple case study, with a qualitative approach, data collection was through the focus group, carried out with seven nurses working in hemodialysis clinics, after approval by the Research Ethics Committee. The analysis of the results was carried out through the collective subject discourse, using the DSCsof 2.0 software. As a result, it was possible to observe that technology facilitates the work process, providing better patient care. There is a counterpoint reported by nurses, that technology, while facilitating the handling of the machine, also makes it difficult, when the nurse does not have technological skills and knowledge. Through the collective subject discourse, it was possible to perceive that nurses indicate technology as something positive in their work process. The technology used in hemodialysis machines provides agility in assistance, providing information about the treatment more effectively, facilitating decision-making. Appropriate treatment methods or technologies is no longer a challenge in the hemodialysis procedure, the current challenges stem from the nurse's mastery in view of the advances in technology that are taking place in relation to hemodialysis machines, which are not used with all their available resources.